Celebrity, Democracy, and Epistemic Power. Issue 1 (March 2020) - Archer, Alfred; Cawston, Amanda; Matheson, Benjamin; Geuskens, Machteld
Abstract : What, if anything, is problematic about the involvement of celebrities in democratic politics? While a number of theorists have criticized celebrity involvement in politics, none so far have examined this issue using the tools of social epistemology, the study of the effects of social interactions, practices, and institutions on knowledge and belief acquisition. We will draw on these resources to investigate the issue of celebrity involvement in politics, specifically as this involvement relates to democratic theory and its implications for democratic practice. We will argue that an important and underexplored form of power, which we will call epistemic power, can explain one important way in which celebrity involvement in politics is problematic. This is because unchecked uses and unwarranted allocations of epistemic power, which celebrities tend to enjoy, threaten the legitimacy of existing democracies and raise important questions regarding core commitments of deliberative, epistemic, and plebiscitary models of democratic theory. We will finish by suggesting directions that democratic theorists could pursue when attempting to address some of these problems.